Analytical investigation and parametric study on the fire behavior of glulam bolted beam-to-column connections based on the quasi-non-linear fracture mechanics model. (October 2022) - Luo, Jing; Li, Zheng; He, Minjuan; Gan, Zhaozhuo; Wang, Xijun
Abstract: In this study, an analytical approach is developed to estimate the fire resistance of glulam bolted connections under coupled shear force and bending moment. This approach includes the combined finite-element heat-transfer model and load-carrying capacity theoretical model. Considering embedment failure and splitting failure as observed in fire tests, a combination of Johansen's model and quasi-non-linear fracture mechanics model is further developed in the proposed approach. The model is validated by experiments, and the comparison between theoretical results and experimental data shows good agreement. Parametric analysis is conducted to investigate different design parameters (e.g., the wood member thickness, the edge distance of the bolts and the load distance) that influence the load-carrying capacity of the connection in fire. Results show that increasing the thickness of wood member is an effective way to obtain better fire performance. The bolt edge distance has little influence on the resistance ratio (Rfire /R20°C ) at the beginning of the fire process (Time ≤15 min) as long as the connection satisfies the minimum requirement of the edge distance of 4 d in Chinese code (GB/T50708-2012). The influence of edge distance becomes evident with the time in fire increases (Time >15 min).